Οικογενειακές γλωσσικές πολιτικές Αλβανών μεταναστών: το σύνθετο τοπίο της γλωσσικής χρήσης ανάμεσα σε γονείς και παιδιά - Χατζηδάκη , Ασπασία; Τζωρτζινάκη , Δήμητρα (Παιδαγωγικά ρεύματα στο Αιγαίο, 2024)
Τhe paper presents a small-scale study on eight families of Albanian immigrants living in Crete, Greece, and their family language policies. The study draws from Bernard Spolsky’s framework and more recent approaches which foreground the children’s agency in shaping the family’s language policies. Our findings corroborate previous research among Albanian families in Greece showing that despite the dominance of the Greek language among second-generation speakers, the ethnic language is still very much in use in many families. In this paper we focus on the various patterns which arise with regard to communication between parents and children and on the ways in which the children’s language dominance and preference seem to interfere with the parents’ desires to maintain the ethnic language at home.